Analisis Tingkat Kepuasan Guru terhadap Upaya Peningkatan Kualitas Pendidikan - Asmawati; D., Hamidah; Afni, Khairina (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study aims to analyze the level of teacher satisfaction in relation to efforts to improve the quality of education at Esa Prakarsa Private High School. Employing a descriptive qualitative design, the research involves five teachers and the school principal as key participants. Data were collected through observations, interviews, questionnaires, and documentation, while the data analysis process followed the stages of data reduction, data display, and conclusion drawing/verification. The findings show that teacher satisfaction regarding initiatives to enhance educational quality demonstrates a consistently positive tendency. Questionnaire results from the five teachers produced an average score of 81.6%, indicating a good level of satisfaction across dimensions such as leadership, work environment, professional support, and availability of educational facilities. Meanwhile, the principal's questionnaire score reached 96%, reflecting a very high level of satisfaction with the overall quality improvement strategies implemented in the school. These results suggest that institutional efforts ranging from instructional development to organizational management have been perceived as effective by the teaching staff and contribute meaningfully to strengthening the school’s quality of education.